A Review of Strategies to Improve Stroke Care Services in Low and Middle-Income Countries: The Innovative Experience of LGH Stroke Programme - Ahmad , Saima; Muda, Ahmad Sobri; Rashid, Umair; Churojana , Anchalee; Mansour , Ossama Yasin; Shah, Husnain Haider (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
This manuscript aims to outline how pre-existing resources can be used for stroke care and how public and government awareness can be raised (influencer model). We likewise portray the achievement of the LGH stroke program as an example of advancement. In LGH, reperfusion treatment has begun in recent years and this paper portrays the one of a kind experience in Pakistan. The aim of this study is to do a comparative analysis between Pakistan, Thailand and Egypt and their approaches to stroke care management and treatment. These countries fall under similar economic standing (LMICs) but Egypt and Thailand have relatively better healthcare systems for stroke management as compared to Pakistan. Hence, this paper looks into these differences and presents potential solutions to how stroke care management can be improved in Pakistan. Additionally, current stroke management in Pakistan is reviewed.